2013
DOI: 10.1097/rli.0b013e3182856a06
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Contrast-Enhanced MRI of the Liver in Mrp2-Deficient Rats Using the Hepatobiliary Contrast Agent Gd-EOB-DTPA

Abstract: The utility of noninvasive DCE-MRI with Gd-EOB-DTPA as a tool for the assessment of Mrp2-deficient hyperbilirubinuria rats was demonstrated. We also clarified that the lower vascular density in the EHBRs may cause delayed uptake of the contrast agent compared with the control rats. In addition, the lower Mrp2 transporter expression may cause the lower efflux of the contrast agent from the Mrp2-deficient rats compared with the control rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 27 publications
1
17
1
Order By: Relevance
“…However, previous studies showed that RE values by Gd-EOB-DTPA could reflect hepatocyte function and had negative correlation with liver fibrosis stage [23]. A previous study with SD (Sprague Dawley) rats found that the peak signal intensity of liver with Gd-EOB-DTPA were at 5 minutes after administration [31], in our study it was about 2 to 3 minutes after administration. It is possible that sample selection bias, motion artifact, region of interest placement result in the different findings between the two studies.…”
Section: Discussioncontrasting
confidence: 40%
“…However, previous studies showed that RE values by Gd-EOB-DTPA could reflect hepatocyte function and had negative correlation with liver fibrosis stage [23]. A previous study with SD (Sprague Dawley) rats found that the peak signal intensity of liver with Gd-EOB-DTPA were at 5 minutes after administration [31], in our study it was about 2 to 3 minutes after administration. It is possible that sample selection bias, motion artifact, region of interest placement result in the different findings between the two studies.…”
Section: Discussioncontrasting
confidence: 40%
“…These data are in line with a recently published study. 12 We assume that the physiological substrates of Oatp1a1 such as bilirubin or bile acid may have delayed hepatic enhancement by Gd-EOB-DTPA by competition with the respective uptake transporter as the Mrp2-deficient rats are experiencing hyperbilirubinemia leading to jaundice. 21,47,48 In a second part of our studies, we have screened Gd-EOB-DTPA with the speculative intention that the contrast agent might be orally absorbed at least to a minimal extent as other strong anionic compounds (eg, bisphosphonates).…”
Section: Discussionmentioning
confidence: 99%
“…10 After hepatocellular uptake, the contrast agent is secreted into bile most likely by the apical (canalicular) efflux carrier MRP2 as concluded from the results of pharmacokinetic studies in Mrp2-difficient rats. 11,12 Affinity to human MRP2 in a more specific in vitro model (eg, MRP2 vesicles) has not been measured so far. It is still unknown how Gd-EOB-DTPA is eliminated from hepatocytes if the canalicular MRP2 is impaired.…”
mentioning
confidence: 96%
“…Its active secretion into bile in rats is via the apical transporter Mrp2 [120] and it is presumed that the human ortholog (MRP2) mediates its biliary excretion in humans. The extensive biliary clearance of gadoxetate (healthy human: 50% of administered dose [101]) facilitates its use for evaluation of hepatobiliary transporter inhibition by drugs as a DILI risk factor [32,33].…”
Section: Current Clinical Use Of Gadoxetate In Liver Disease Diagnosismentioning
confidence: 99%